Genesis of apartheid: History and Race in South Africa - (:unkn) unknown (My University, 2020)
Since the landing in South Africa of Europeans in 1652, the country has based the relationship of the different groups that live on its soil on the notion of “race”. It is in 1685 that the Dutch East India Company forbade mixed marriages in its station in the Cape. All along their history, miscegenation has been a worry for White people in South African, whether they be Dutch or British settlers. It has thus induced the different White governments to segregate the various groups under its authority, Africans, Coloureds or “Asians”. This article aims at examining the mechanisms that led to the discrimination policies that have anticipated the Apartheid regime. The objective will be both to understand le political and economic issues at stake, but also the ideological one which led the leaders of a minority group, the Whites, to try to define the notion of “race” in order to justify their project.
Keywords: African Research